PERBEDAAN EKSPRESI P53 ANTARA STADIUM KLINIS III DAN IV PENDERITA KARSINOMA NASOFARINGS - , Hesty Setiyarini, Dr. dr. Bambang Hariwiyanto, Sp.THT-KL(K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The prevalence of NPC in Indonesia is 4.7 per 100,000 population each year. One of the factors as the cause of nasopharyngeal carcinoma is the inactivation of the p53 suppressor gene that can cause by p53 mutations, thus eliminate the function of p53 wild-suppressor which then continues to malignancy process in nasopharynnx. P53 protein is functioned to control cell cycle regulation and apoptosis. Inactivation of these genes cause apoptosis disturbance and increases cell proliferation. Alteration of p53 expression have been found in nasopharyngeal carcinoma. Aims: This study was aimed to assess the P53 protein expression difference between III and IV clinical stage in nasopharyngeal carcinoma. Methods: The study design was cross-sectional. Data that was taken as many as 30 samples of nasopharygeal carcinoma patients from medical records, and patient paraffin blocks that has been available in The Department of Pathology Anatomy Dr. Sardjito General Hospital Yogyakarta were done an immunohistochemical examination (IHC) using concentrated Monoclonal Antibody p53 (Clone DO -7) to see the expression of P53. P53 expression differences then were examined the differences between III and IV clinical stage. Statistical analysis used independent sample t-test. Result: From this study have been found samples in stage III as many as 12 samples patients (40%), stage IV 18 samples patients (60%). P53 esxpression has been found in 30 samples (100%), There were differences of p53 expression between III and IV clinical stage in nasopharyngeal carcinoma, showed no statistically significant (p = 0.232). Conclusion: There are no statistically significant differences in p53 expression betweenclinical stage III and IV in nasopharyngeal carcinoma patients. Keywords : Nasopharyngeal Carcinoma, NPC, p53 expression, immunohistochemical, clinical stage III and IV